Impact of Academic Integration and Social Engagement on Student Persistence at Historically Black Colleges and Universities during COVID-19 Pandemic - Wilkes, Marques J.; Okojie, Felix A. (Advances in Social Sciences Research Journal, 2023)
The purpose of this study was to explore the impact that academic integration and social engagement had on student persistence at historically black colleges and universities during the COVID-19 pandemic. The Social Engagement Theory guided a qualitative examination to answer two research questions: 1) How did academic integration impact the persistence of students at Historically Black Colleges and Universities during COVID-19 pandemic? 2) How did social engagement impact the persistence of students at Historically Black Colleges and Universities during COVID-19 pandemic? Interviews with twelve study participants shed light on their experience on their college campuses before the COVID-19 pandemic and upon their return to campus. This was important to understand how students interacted with each other and their instructors and advisors before campuses were closed due to a global pandemic. It was also important to understand how students interacted with one another once they returned to campus after being away and transitioning to a remote-working and remote-learning environment. Responses to the research questions provided value on how the study participants shifted their levels of engagement and ability to be more independent, self-aware and cautious with and around others. Participants also shared how their experiences upon return to campus affected their ability to focus and persist toward graduation. Braxton et al. (2000) research shared students believed participating in class discussions had a positive impact on their social integration and persistence. Further, there was evidence that students’ subsequent commitment to their institution positively impacted their motivation to complete their degrees. This study increases the knowledge to provide information to HBCUs who may not have the infrastructure in place and resources to make it through a global pandemic.